REALISM IN RUSSIAN LITERATURE: THE ROLE OF A.S.PUSHKIN AND L.N.TOLSTOY (TAMADDUN NURI JURNALI, 2025)
This article examines the emergence and development of realism in 19th-century Russian literature through the lens of the works of two key figures – Alexander Sergeyevich Pushkin and Leo Nikolaevich Tolstoy. It analyzes their artistic methods, themes, characters, and philosophical ideas that contributed to the formation of a unique path of Russian realism. Special attention is paid not only to the historical context but also to the deep aesthetics of the realist movement in their works.